Bystander interventions and survival after exercise-related sudden cardiac arrest: a systematic review. Issue 7 (1st December 2021) - Grubic, Nicholas; Hill, Braeden; Phelan, Dermot; Baggish, Aaron; Dorian, Paul; Johri, Amer M
Abstract : Objective: To evaluate the provision of bystander interventions and rates of survival after exercise-related sudden cardiac arrest (SCA). Design: Systematic review. Data sources: MEDLINE, EMBASE, PubMed, CINAHL, SPORTDiscus, Cochrane Library and grey literature sources were searched from inception to November/December 2020. Study eligibility criteria: Observational studies assessing a population of exercise-related SCA (out-of-hospital cardiac arrests that occurred during exercise or within 1 hour of cessation of activity), where bystander cardiopulmonary resuscitation (CPR) and/or automated external defibrillator (AED) use were reported, and survival outcomes were ascertained. Methods: Among all included studies, the median (IQR) proportions of bystander CPR and bystander AED use, as well as median (IQR) rate of survival to hospital discharge, were calculated. Results: A total of 29 studies were included in this review, with a median study duration of 78.7 months and a median sample size of 91. Most exercise-related SCA patients were male (median: 92%, IQR: 86%–96%), middle-aged (median: 51, IQR: 39–56 years), and presented with a shockable arrest rhythm (median: 78%, IQR: 62%–86%). Bystander CPR was initiated in a median of 71% (IQR: 59%–87%) of arrests, whereas bystander AED use occurred in a median of 31% (IQR: 19%–42%) of arrests. Among the 19 studies that reported survival to hospital discharge, the median rate of survival was 32% (IQR: 24%–49%). Studies which evaluated the relationship between bystander interventions and survival outcomes reported that both bystander CPR and AED use were associated with survival after exercise-related SCA. Conclusion: Exercise-related SCA occurs predominantly in males and presents with a shockable ventricular arrhythmia in most cases, emphasising the importance of rapid access to defibrillation. Further efforts are needed to promote early recognition and a rapid bystander response to exercise-related SCA.